A Nanoscale Study of Carbon and Nitrogen Fluxes in Mats of Purple Sulfur Bacteria: Implications for Carbon Cycling at the Surface of Coastal Sediments - Hubas, Cédric; Boeuf, Dominique; Jesus, Bruno; Thiney, Najet; Bozec, Yann; Jeanthon, Christian (Frontiers in Microbiology, 2017)
Mass blooms of purple sulfur bacteria growing seasonally on green stranded macroalgae have a major impact on the microbial composition and functionality of intertidal mats. To explore the active anoxygenic phototrophic community in purple bacterial mats from the Roscoff Aber Bay (Brittany, France), we conducted a combined approach including molecular and high-resolution secondary ion mass spectrometry (NanoSIMS) analyses. To investigate the dynamics of carbon and nitrogen assimilation activities, NanoSIMS was coupled with a stable isotope probing (SIP) experiment and a compound specific isotope analysis (CSIA) of fatty acid methyl ester (FAME). Sediment samples were incubated with 13C- and/or 15N-labelled acetate, pyruvate, bicarbonate and ammonium. NanoSIMS analysis of 13C - and 15N -incubated samples showed elevated incorporations of 13C - and 15N in the light and of 13C -acetate in the dark into dense populations of spherical cells that unambiguously dominated the mats. These results confirmed CSIA data that ranked vaccenic acid, an unambiguous marker of purple sulfur bacteria, as the most strongly enriched in the light after 13C -acetate amendment and indicated that acetate uptake, the most active in the mat, was not light-dependent. Analysis of DNA- and cDNA-derived pufM gene sequences revealed that Thiohalocapsa-related clones dominated both libraries and were the most photosynthetically active members of the mat samples. This study provides novel insights into the contribution of purple sulfur bacteria to the carbon cycle during their seasonal developments at the sediment surface in the intertidal zone.